Optimum Choice of Energy System Configuration and Storages for a Proper Match between Energy Conversion and Demands - Toffolo, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue addresses the general problem of a proper match between the demands of energy users and the units for energy conversion and storage, by means of proper design and operation of the overall energy system configuration. The focus is either on systems including single plants or groups of plants, connected or not to one or more energy distribution networks. In both cases, the optimum design and operation involve decisions about thermodynamic processes, about the type, number, design parameters of components/plants, and storage capacities, and about mutual interconnections and the interconnections with the distribution grids. The problem is absolutely general, encompassing design and operation of energy systems for single houses, groups of houses, industries, industrial districts, municipal areas, regions and countries. The presented papers show that similar approaches can be used in different applications, although a general standard has not been achieved yet.